Targeting Autophagy as a Strategy for Developing New Vaccines and Host-Directed Therapeutics Against Mycobacteria - Strong, Emily J.; Lee, Sunhee (Frontiers in Microbiology, 2021)
The mycobacterial disease is a significant burden worldwide. This disease group includes tuberculosis, leprosy (Hansen’s disease), Buruli Ulcer, and Nontuberculous mycobacterial (NTM) disease. The burden of NTM disease, both pulmonary and ulcerative, is significantly escalating globally, especially in developed countries such as America and Australia. The concern is the drastic rise of multiple drug-resistant and extensively drug-resistant tuberculosis infections and increased disease presentation with HIV and diabetes. Mycobacteria’s ability to inhibit or evade the host immune system has contributed significantly to its continued prevalence. Autophagy is a complex conserved cellular process. While considered a cellular survival mechanism, its dysregulation can lead to cell death. Autophagy affects many facets of host health, including roles in aging, cancer, and response to intracellular pathogens, such as mycobacteria. Additional understanding of the role of critical host cell pathways such as autophagy could be utilized to further develop treatments or vaccines against the broad spectrum of mycobacterial disease.